Study of sub-auroral dynamics using integrated measurements - Behera, Jayanta Kumar (Indian Institute of Geomagnetism (IIG), 2016)
Particle precipitation at high latitude in the various energy band (e.g. 10 KeVs to 10s of MeV) and corresponding changes in the electrodynamics of the Ionosphere has always been the major concerned in solar terrestrial science. There are various types of processes that con tributes to precipitation of charge particles either electrons or protons or both at high latitude. High latitude atmosphere has direct access to the magnetospheric charged particle either by open field lines or closed field lines depending upon their relative position to the geomag netic poles, for example polar cap has direct access to the incoming plasma from the sun, where as auroral latitude get affected by the closed field line precipitation by the formation of substorm current weidge. Additionally, the electrons associated with central plasma sheet, being injected in the night side of the magnetotail, mostly in midnight hours and further fall into loss cone during gradient-curvature drift in the inner magnetosphere and subsequently precipitate in to the auroral atmosphere. All these processes not only make high latitude iono sphere complex but also make the study of high latitude ionosphere much more interesting and important. Adding things to the importance of high latitude ionosphere and related space weather processes, now-a-days, impact of these space weather activity on the climate change is getting attention from the scientific community. Many workers [Sheila et al, 2015] already confirmed that enhanced Precipitating particles during high speed solar wind (HSS) events affect the neutral chemistry of the polar middle atmosphere. In last few decades, it has been shown that production of NOx in the mesosphere region during the precipitation of charged particles (with energy range >30 KeV to 1 MeV) [Meredith et al., 2011] is directly related to the ozone loss in the polar middle atmosphere, extending from mesosphere to upper strato sphere [Rodger et al., 2007]. A decade has already elapsed for the geomagnetic study at the second permanent Indian Antarctic research station, Maitri. The geomangetic study at that location(L= 5; CGM 62.45◦ S, 55.45◦ E), which is a sub-auroral location is strategically important for Auroral subsotrm dynamics and related particle precipitation study. However, presence of a single digital flux gate Magnetometer (DFM) and a wide beam riometer could not serve this purpose. India had its first imaging Riometer installed at the Indian Antarctic station, Maitri during Austral summer of 2009-2010. Hence, this thesis is dedicated to explore the dynamics of auroral currents and concurrent particle precipitations over Maitri during geomagnetic disturbances i.e.magnetospheric substorm and geomagnetic storm events using imaging Riometer predominantly along with other measurements such as Ground Magnetometer, satellite observations for interplanetary parameter, Satellite particle flux data, X-ray data and GPS TEC data. There fore, this thesis is an initiative to a process of deep understanding the auroral activity and related particle precipitation at a sub-auroral location, Maitri.
A thesis submitted to the University of Mumbai for the Ph.D.(Science) degree in physics under the guidance of Dr. A.K. Sinha
Keywords: Geomagnetic substorm; Geomagnetic storm; Integrated measurements; Sub-auroral dynamics; Maitri; Antarctica; PhD Thesis